VALIDASI METODE PENENTUAN KADMIUM (Cd) PADA PUPUK ORGANIK PADAT MENGGUNAKAN SPEKTROFOTOMETER SERAPAN ATOM (SSA) DI PT. GLOBAL ENVIRONMENT LABORATORY - Astari Simbolon Monica Magdalena (PROSIDING SEMINAR KIMIA, 2020)
Validation of the method of determining cadmium (Cd) in manure using Atomic Absorption Spectrophotometer (AAS) at PT Global Environment Laboratory has been carried out. The determination of cadmium metal (Cd) in manure refers to the Indonesian National Standard (SNI) 2803: 2012. Based on the results of testing for cadmium (Cd) in manure, the correlation coefficient (r) was 0.9997 and the cadmium (Cd) content obtained was 1.954 mg / kg with a relative standard deviation (RSD)% value of 0.028% less than 2 / 3 CV Horwitz amounted to 2.41. 0Accuracy value ranges from 105.05% to 116.86%. The detection limit value (LOD) was 0.38 mg / kg and the quantization limit value (LOQ) was 0.43 mg / kg. The instrument limit value (IDL) is 0.022 ppm and the method limit value (MDL) is 0.0194 ppm, these results meet the MDL acceptability requirements. Based on the research results, the determination of cadmium (Cd) in manure with the SNI method for solid NPK fertilizers using Atomic Absorption Spectrophotometer (AAS) can be used with valid results. Keywords : Manure, Validation method, Atomic Absorption Spechtrophotometer (AAS), Cadmium (Cd)